Порівняльний аналіз технологій EDR та XDR, частина 1 - Сєров, І. О. (ХНУРЕ, 2023)
The purpose of the study is to analyze modern information security technologies (EDR and XDR) for solving the problems of protecting information in the corporate net infrastructure.
Keywords: технологія EDR; технологія XDR